Inclusive leadership and project success: Mediating and moderating effects - Rehman, Shaikh Aqeeb Ur; Mehmood, Shahid; Shahid, Shiza; Adnan, Adnan; Saleem, Aribah (Edelweiss Applied Science and Technology, 2026)
This study aims to investigate, via empirical means, how inclusive leadership (IL) affects project success (PS), considering the moderating influence of person-job fit (PJF) and the mediating role of project team member silence (PTMS). Data were collected using a questionnaire with a convenience sampling technique. Five hundred employees and project managers working in different project-based organizations in Pakistan’s twin cities of Rawalpindi and Islamabad were chosen to complete the questionnaire. Using SPSS, data were analyzed, and correlation and regression analyses were performed for the relationships in the study. The MACRO process was deployed for testing mediation and moderation in the current research. Results revealed that inclusive leadership has a positive relationship with project success, and project team member silence mediated this relationship. Furthermore, person-job fit moderated the relationship between project team member silence and project success. Although leadership has been widely discussed in literature, and there has been growing interest among researchers in related studies, empirical evidence for the relationship between inclusive leadership and project success remains scarce. Many existing studies are based on non-project companies, leaving a gap in understanding how inclusive behavior can influence project outcomes. The current research fills this gap by deploying a quantitative technique to validate data from project-based organizations in the twin cities of Pakistan.